Model Eliciting Activities: Fostering 21st Century Learners - Micah Stohlmann (Journal of Mathematics Education at Teachers College, 2013)
Real world mathematical modeling activities can develop needed and valuable 21st century skills. The knowledge and skills to become adept at mathematical modeling need to develop over time and students in the elementary grades should have experiences with mathematical modeling. For this to occur elementary teachers need to have positive experiences themselves with mathematical modeling. This paper describes how a four-part 21st century skills framework—innovate, synthesize, adapt, and communicate—was integrated with a mathematical modeling activity that one class of pre-service elementary teachers completed. The pre-service elementary teachers were able to generate a variety of ideas, communicate effectively, and work towards successful solutions by using their resources and prior knowledge.